Sumber Daya Alam dan Kearifan Lokal sebagai Rasional dalam Workshop Visual branding Kawasan Wisata Pantai Plentong Kabupaten Indramayu Jawa Barat - Nanang Ganda Prawira; Arief Johari; Mega Fitriani Adiwarna Prawira; Eko Susanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The tourism development on Plentong Beach, Ujunggebang Village, Sukra District, Indramayu Regency has shown a positive impact on socio-economic and ecological conditions in this region. Collaboration between the Village Government, BUMDES Maju Ujunggebang and the community has been able to turn Plentong Beach into an inclusive tourist destination for the people of the North Coast of West Java. To expand marketing communication and provide visual identity, a visual branding product was designed in Community Service activities by applying the Design Thinking method through observation, interviews, and Focus Group Discussions. This activity has succeeded in designing a visual branding product that will be applied to souvenir products according to the needs and interests of partners. In the future, it is necessary to develop visual branding on marketing communication media in the form of websites, signage, and social media to expand the popularity of Plentong Beach which in turn attracts more visits from wider demographic and geographic segments for the advancement of destinations and people on Plentong Beach.